Politik Islam Dan Demokrasi Elektoral: Studi Fikih Siyasah Di Negara Mayoritas Muslim: - Akhmad Zaki Yamani (STIT Syekh Muhammad Nafis Tabalong, 2025)
This article discusses the integration of fiqh siyasa with the electoral system in the context of Muslim-majority countries. Islamic politics in Indonesia is an important part of the country’s political landscape, reflecting its pluralism and democracy. Islamic politics involves Islamic-based political parties and religious-based groups participating in elections, respecting religious freedom, minority rights, and encouraging interfaith cooperation. Using normative and comparative approaches, this study analyzes how Islamic principles such as deliberation, bai’at, justice, and accountability are applied in modern electoral practices. Case studies in Indonesia, Iran, Turkey, and Malaysia show that despite differences in approach, sharia values can still coexist with democratic systems. However, challenges such as money politics, vote manipulation, and tensions between positive law and religious norms are serious obstacles. Therefore, this article proposes a reconstruction of electoral law that is contextual but still based on Islamic values, by involving the active role of ulama, fatwa institutions, and Islamic parties in creating fair, honest, and dignified elections.